Alguém poderia mim ajuda nessas questão por favor com as resposta completa por favor, mim ajudem.
Anexos:
Respostas
respondido por:
1
.
Ola Dayana
1)
f(x) = 2x
f'(x) = 2
f'(3) = 2 (B)
2)
(x + 1 , x + 2) (4,5)
(z + y, z + 2y) (36,45)
x + 1 = 4
x = 3
z + y = 36
z + 2y = 45
y = 9
z = 27
matriz A
(1 3)
(9 27)
soma S = 1 + 3 + 9 + 27 = 40 (C)
3)
f(x) = 6x^3 + 5x^2 - 7x
f'(x) = 18x^2 + 10x - 7 ((E)
4)
log5(2x + 1) = log5(x + 3)
2x + 1 = x + 3
2x - x = 3 - 1
x = 2 (A)
Ola Dayana
1)
f(x) = 2x
f'(x) = 2
f'(3) = 2 (B)
2)
(x + 1 , x + 2) (4,5)
(z + y, z + 2y) (36,45)
x + 1 = 4
x = 3
z + y = 36
z + 2y = 45
y = 9
z = 27
matriz A
(1 3)
(9 27)
soma S = 1 + 3 + 9 + 27 = 40 (C)
3)
f(x) = 6x^3 + 5x^2 - 7x
f'(x) = 18x^2 + 10x - 7 ((E)
4)
log5(2x + 1) = log5(x + 3)
2x + 1 = x + 3
2x - x = 3 - 1
x = 2 (A)
dayana24:
Muito obrigado .
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás